Attachment and propensity for reporting compassionate opportunities and behavior in everyday life - Varley, Deanna; Sherwell, Chase S.; Kirby, James N. (Frontiers in Psychology, 2024)
Researchers have identified links between anxious and avoidant attachments and difficulties with self-compassion, giving others compassion, and receiving compassion. However, while compassion requires both awareness of opportunities for compassion and compassionate action, little is known about attachment-related differences in reporting compassionate opportunities. Further, most research relies on retrospective-reports that may not accurately assess compassionate behaviours in everyday life. Method:Consequently, we collected 2757 experience sampling survey responses from 125 participants (95 women, 27 men, 3 non-binary, Mage = 18.74, SDage = 1.66) to investigate whether attachment anxiety, avoidance, or their interaction were associated with differences in propensity for reporting compassionate opportunities, actions, and emotional responses to opportunities in everyday life across self-compassion, giving compassion, and receiving compassion. Results: Anxiety was associated with greater likelihood of reporting all types of compassionate opportunities and less positive responses to opportunities to receive compassion. Avoidance was associated with less likelihood of reporting opportunities to give and receive compassion and less positive responses to opportunities to give compassion.Those high in anxiety but simultaneously low in avoidance reported fewer selfcompassionate actions, but we identified no further differences in compassionate action.Discussion: This study highlights the potential role of awareness of compassionate opportunities in attachment-related differences in compassion.